2016
DOI: 10.1089/wound.2013.0492
|View full text |Cite
|
Sign up to set email alerts
|

Refined Spruce Resin to Treat Chronic Wounds: Rebirth of an Old Folkloristic Therapy

Abstract: Significance: The treatment of chronic wounds results in an enormous drain on healthcare resources in terms of workload, costs, frustration, and impaired quality of life, and it presents a clinical challenge for physicians worldwide. Effective local treatment of a chronic wound has an important role, particularly in patients who are-because of their poor general condition, diminished life expectancy, or unacceptable operative risk-outside of surgical treatment. Recent Advances: Since 2002, our multidisciplinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 25 publications
0
32
0
2
Order By: Relevance
“…Resins derived from coniferous trees are phytochemicals that were used since ancient times in Asian and Scandinavian traditional human medicine. These resin-based products are mainly used for treating wounds, sores, pressure ulcers and a variety of other skin problems [2022]. Recent scientific research has confirmed the efficacy of these compounds, both in human clinical trials as well as in animal models and in vitro [20, 2326].…”
Section: Introductionmentioning
confidence: 99%
“…Resins derived from coniferous trees are phytochemicals that were used since ancient times in Asian and Scandinavian traditional human medicine. These resin-based products are mainly used for treating wounds, sores, pressure ulcers and a variety of other skin problems [2022]. Recent scientific research has confirmed the efficacy of these compounds, both in human clinical trials as well as in animal models and in vitro [20, 2326].…”
Section: Introductionmentioning
confidence: 99%
“…They were identified as p-coumaric acid (1), caffeic acid (2), and ferulic acid (3). Sub-fraction 2 consisted mostly of pinoresinol (4), which was isolated by preparative TLC. Sub-fraction 5 contained the DHAA derivatives 7α,15-dihydroxy-DHAA and 7β,15-dihydroxy-DHAA, which were isolated by flash chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…The resinous excretion of Norway spruce (Picea abies (L.) H. Karst., Pinaceae) [3] has a long-standing history in the treatment of skin ulcers and infected wounds [4]. Lipophilic preparations using butter or swine lard as ointment base were and still are known as an effective cure for acute and chronic wounds.…”
Section: Norway Spruce Balm: Phytochemical Composition and Ability Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there here has been increasing interest in the secondary chemistry of P. sylvestris and P. abies as a source of bioactive compounds [ 1 ]. Specifically, the wood extractives of these species have shown to have antibacterial properties against methicillin-resistant Staphylococcus aureus and Escherichia coli [ 2 ] and P. abies resin-based salve has been proven to be clinically effective for the treatment of chronic wounds [ 3 ]. The defensive chemistry of coniferous species consists of all three major secondary chemistry groups—phenolics (e.g., acetophenones, lignans, stilbenes, flavonoids, phenolic acids and proanthocyanidins), terpenes (e.g., monoterpenes and resin acids) and alkaloids (piperidines) but the bioactive compounds responsible for antimicrobial properties have been assumed to be phenolic and terpene compounds [ 1 ].…”
Section: Introductionmentioning
confidence: 99%